CAR-T cell therapy for rheumatoid arthritis: current status and molecular insights: CAR-T cell therapy in RA: a concise review - Blagov, Alexander V.; Pleshko, Elizaveta M.; Maltseva, Olga N.; Asoyan, Alikhan Z.; Ravani, Alessio L.; Orekhov, Alexander N. (Cellular and Molecular Biology, 2025)
Chimeric antigen receptor (CAR)-T cell therapy, a breakthrough in hematological cancer treatment, is now being explored for autoimmune diseases like rheumatoid arthritis (RA). RA, characterized by chronic joint inflammation and autoantibody production, presents a compelling target for CAR-T cell therapy due to its potential for precise targeting of aberrant immune cells and restoration of immune tolerance. This review analyzes current strategies in CAR-T cell therapy for RA, focusing on molecular mechanisms and clinical implications. We discuss approaches such as CD19-targeted B cell depletion, simultaneous targeting of B cells and memory plasma cells, and the use of chimeric autoantibody receptors (CAARs) to target specific autoantigens. Furthermore, we explore the latest advancements in CAR-T cell engineering, including novel costimulatory domains, dual-targeting strategies, and the development of regulatory CAR-T cells (CAR-Tregs). This review provides insights into the efficacy and safety of CAR-T cell therapy for RA, highlighting its potential to revolutionize clinical applications and future directions in the field.